Puffing and microexplosion behavior of water in pure diesel emulsion droplets during leidenfrost effect - Yahaya Khan, M. (Taylor and Francis Inc., 2017)
The microexplosion evolution phenomenon of single droplets of water in pure diesel emulsion under Leidenfrost effect has been studied. The tested emulsions were stabilized with a blend of commercial surfactants with three different water contents of 9, 12, and 15. A high speed camera synchronized with backlight technique was used to capture the evolution of microexplosion and puffing. Three different droplet diameters of approximately 2.6 mm, 2 mm, and 0.2 mm were analyzed. It was found that the tendency of microexplosion and puffing frequency was influenced by the droplet diameter. Coalescence was the dominating factor in inducing microexplosion in bigger droplets. It was observed that the child droplets ejected from the parent droplet undergoes further puffing processes. The size of the secondary droplets after microexplosion were also found to be slightly influenced by the parent droplet size. The waiting time for microexplosion and puffing were compared for different droplets size. © 2017 Taylor & Francis.